Faktor-faktor yang berhubungan dengan hardiness perawat di rumah sakit: A literature review - Syafni, Syafni; Bayhakki, Bayhakki; Lestari, Widia (Holistik Jurnal Kesehatan, 2024)
Background: Hardiness or mental resilience is an individual's ability to manage, overcome, reduce and survive stress or unpleasant conditions in life. The task of nurses in nursing practice is to provide nursing care to overcome both physical and psychological problems of patients, requiring a strong nurse personality and good work resilience. Purpose: To determine the factors associated with the hardiness of nurses working in hospitals. Method: Literature review research uses the PICO (Population/problem) method in searching for articles. The inclusion criteria for articles were that they were published in 2019-2023, had full text available, in Indonesian or English, and used quantitative or qualitative research methods carried out on nurses working in hospitals. The keywords used for the search were "hardiness, nurse, hospital". Searching articles through the Google Scholar and ProQuest databases, found 10 articles. Results: The results of the analysis showed factors that were associated with hardiness in nurses who worked in hospitals were family social support, nurse reliability, leadership, work experience, hardiness also associated with work stress, emotional labor, and nurse burnout. Conclusion: Hardiness is related to work stress, family social support, and is related to nurse resilience. In addition, it can reduce the impact of emotional labor, affect the occurrence of burnout, and is also influenced by leadership and dealing with work situations such as a pandemic outbreak.   Keyword: Hardiness; Hospital; Nurse.   Pendahuluan: Hardiness atau ketahanan mental adalah kemampuan individu dalam mengelola, mengatasi, mengurangi, dan bertahan dari stres atau kondisi yang tidak menyenangkan dalam hidup. Tugas perawat dalam praktek keperawatan yaitu melakukan asuhan keperawatan untuk mengatasi masalah baik fisik maupun psikologis dari pasien, membutuhkan kepribadian perawat yang kuat serta ketahanan kerja yang baik. Tujuan: Untuk mengetahui faktor yang berhubungan dengan hardiness pada perawat yang bekerja di rumah sakit. Metode: Penelitian studi literature review menggunakan metode PICO (Population/problem) dalam mencari artikel. Kriteria inklusi artikel adalah diterbitkan tahun 2019-2023, tersedia full text, bahasa Indonesia atau bahasa Inggris, dan menggunakan metode penelitian kuantitatif atau kualitatif dilakukan terhadap perawat yang bekerja di rumah sakit. Kata kunci yang digunakan untuk pencarian adalah “hardiness, perawat, rumah sakit, nurse, hospital”. Penelusuran artikel melalui database Google Scholar dan ProQuest, ditemukan sebanyak 10 artikel. Hasil: Faktor yang hubungan dengan hardiness pada perawat yang bekerja di rumah sakit adalah dukungan sosial keluarga, resiliensi perawat, kepemimpinan, pengalaman kerja, hardiness juga berhubungan dengan stres kerja, emotional labor, burnout perawat Simpulan: Hardiness berhubungan dengan stress kerja, dukungan sosial keluarga, dan berhubungan dengan resiliensi perawat. Selain itu, dapat mengurangi dampak dari emotional labor, berpengaruh terhadap terjadinya burnout, dan dipengaruhi juga oleh kepemimpinan serta menghadapi situasi kerja seperti adanya wabah pandemi.   Kata Kunci: Ketahanan; Perawat; Rumah Sakit.